534 Takotsubo syndrome secondary to vaccination for SARS-CoV-2. (8th December 2021) - Torselletti, Lorenzo; Giulia, Stronati; Corraducci, Francesca; Belleggia, Sara; Maiorino, Francesco; Casella, Michela; Dello Russo, Antonio; Guerra, Federico
Abstract: Methods and results: A 79-year-old woman, with a history of subclinical hypothyroidism, obesity and smoke presented to the Emergency Room with dyspnoea and cold sweating. She had undergone her first dose of COVID-19 Moderna mRna vaccination just four days prior to her admission. She showed elevated HS troponin and elevated BNP at her laboratory exams. Her 12-lead ECG showed T wave inversion in the antero-lateral leads and prolongued QTc. Her transthoracic echocardiogram showed severe ejection fraction reduction due to hypokinesia of the mid-apical segments of the anterior and lateral walls of the heart. The patient was then admitted to the Cardiology ward in order to perform a coronary angiography which sowed no significant coronary stenosis. She was started on appropriate medication and discharged after a six day in-hospital stay. At discharge she showed partial recovery of her ejection fraction (EF 44%). A cardiac magnetic resonance was performed after discharge which showed no late gadolinium enhancement. Such finding allowed us to rule out the diagnosis of myocarditis. Moreover at her 3-month follow-up her ejection fraction had recovered completely. We concluded for the diagnosis of Takotsubo Syndrome secondary to vaccination. Conclusions: We presented a case of Takotsubo syndrome after vaccination with the Moderna vaccine for COVID-19. Two other similar case reports can be found in current medical literature. Female sex, post-menopausal age and the inevitable psychological stress derived by the pandemic and the vaccination may have triggered the condition.